2009
DOI: 10.1177/1470595808101158
|View full text |Cite
|
Sign up to set email alerts
|

Constraints in the Implementation of Performance Management Systems in Developing Countries

Abstract: Performance management has become a key element in modern public sector governance. As a result, many developing countries have introduced it as a means to measure organizational and individual efficiency in order to ensure that public sector organizations meet the needs of the public. However, the implementation of performance management systems in many of these countries has been affected by a number of institutional and capacity constraints such as culture, institutional fragmentation, public apathy, and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(114 citation statements)
references
References 56 publications
(51 reference statements)
4
107
1
2
Order By: Relevance
“…Ohemeng (2009) has identified culture, institutional fragmentation, the lack of institutionalized sanctions and rewards, and lack of political will or commitment as some of the problems that affected the implementation of the program. The lack of political commitment was compounded by a similar attitude among managers, and by the overall problem of people management.…”
Section: Ijppm 613mentioning
confidence: 98%
“…Ohemeng (2009) has identified culture, institutional fragmentation, the lack of institutionalized sanctions and rewards, and lack of political will or commitment as some of the problems that affected the implementation of the program. The lack of political commitment was compounded by a similar attitude among managers, and by the overall problem of people management.…”
Section: Ijppm 613mentioning
confidence: 98%
“…The findings indicate that some MMDAs PM systems are more effective than others and they tend to performance better (Ohemeng, 2009). This implies that while PM may be a tool to ensure high-performance culture among MMDAs, some local government authorities may not have the same level of capacity to succeed in this regard (Fryer et al, 2009) due to technical and resource limitations (Ohemeng, 2011) to institutionalise PM in their internal business process (Cavalluzzo and Ittner, 2004;Ter Bogt, 2008;Brignall and Modell, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To achieve value for money and best managerial practices, the adoption of new public management (NPM) reforms in the public service have been phenomenal (Annan-prah and Ohemeng, 2015;Ayee, 2001;Domfeh, 2004;Ohemeng, 2009;Rhodes et al, 2012;Simpson and Buabeng, 2013). Therefore, this study examines the results of MMDAs PM and the challenges if any that they are confronted with in their efforts to institutionalise performance culture in local governance.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…While the principles that underlie the drive for performance management are assumed to be universal, nevertheless scholars have shown that the cultural environment of a given public sector as well as its historical features can affect the success with which performance management reforms are introduced (Ohemeng 2009;Pollitt 2005;Ho and Im 2013). Moreover, with regard to South Korea, the implementation of reforms based on the NPM ideology is particularly notable, as it was long assumed that the relatively unique developmental model of Korea and other East Asian countries had produced an administrative environment incompatible with the underlying principles of NPM style reform (Park and Joo 2010).…”
Section: Results-based Reform and The Korean Public Sectormentioning
confidence: 99%